2017
DOI: 10.5424/sjar/2016144-9714
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evaluation of phosphate-solubilizing bacteria from grapevine rhizospheres for use as biofertilizers

Abstract: Phosphate-solubilizing bacteria (PSB) have the ability to solubilize insoluble phosphorus (P) and release soluble P. Extensive research has been performed with respect to PSB isolation from the rhizospheres of various plants, but little is known about the prevalence of PSB in the grapevine rhizosphere. In this study, we aimed to isolate and identify PSB from the grapevine rhizosphere in five vineyards of Northwest China, to characterize their plant-growth-promoting (PGP) traits, evaluate the effect of stress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 51 publications
(57 reference statements)
1
29
0
1
Order By: Relevance
“…The indigenous PSB in combination with chemical fertilizer (superphosphate and rock phosphate) reduces dose requirement by 25-50% (Sundara et al 2002). Some studies reported that inoculation of PSB can solubilize the Ca/Mg/Al/Fe-bound P which becomes available to the plant roots for growth enhancement and root proliferation (Liu et al 2016). The release of enzymes and other chemicals by PSB (organic acids, phosphorus-solubilizing enzymes, phytase, and siderophore) breaks down the bond between P and the fixing element to make it available for the plant uptake (Hayes et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The indigenous PSB in combination with chemical fertilizer (superphosphate and rock phosphate) reduces dose requirement by 25-50% (Sundara et al 2002). Some studies reported that inoculation of PSB can solubilize the Ca/Mg/Al/Fe-bound P which becomes available to the plant roots for growth enhancement and root proliferation (Liu et al 2016). The release of enzymes and other chemicals by PSB (organic acids, phosphorus-solubilizing enzymes, phytase, and siderophore) breaks down the bond between P and the fixing element to make it available for the plant uptake (Hayes et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…From previous research, a specific B. arybhattai strain isolated from grapevine rhizospheres was considered a potential biofertilizer because it showed various PGP abilities such as nitrogen fixation and the production of IAA, siderophores, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, chitinase, and protease [51]. Another B. arybhattai strain SanPS1 also isolated from soil showed chlorpyrifos and malathion degradation ability [52].…”
Section: Discussionmentioning
confidence: 99%
“…deaminase, chitinase, and protease [51]. Another B. arybhattai strain SanPS1 also isolated from soil showed chlorpyrifos and malathion degradation ability [52].…”
Section: Effect Of Fungicides On Iaa Production Of Mn1mentioning
confidence: 99%
“…The capability of rhizobacteria to solubilize insoluble phosphates has been of interest to agricultural microbiologist as it can enhance the availability of phosphorus for the plant to improve plant growth and yield [29]. It has been reported that higher concentrations of phosphate-solubilizing bacteria are commonly found in the rhizosphere as compared to bulk soil [30].…”
Section: Discussionmentioning
confidence: 99%